Content management systems in education - Mateljan, Vladimir; Đambić, Goran; Juričić, Vedran (2008)
Constant improvements and increase of available features of content management systems resulted in their growing application in various sectors. This paper analyzes today’ s content management systems in order to find the characteristics that are common to the majority of those systems, and to find what characteristics make them suitable for usage in online education. To provide this, authors analyzed great number of content management systems and their characteristics, and made a comparison of content management systems based on supporting operating systems, approximate cost and popularity. The analyses show that the most represented and most appreciated characteristics are interoperability, support and existence of applications that are optional, but can be integrated with existing site, and that provide additional functionalities, like events calendar, newsletters and blogs.
Projekt MZOS
Projekt MZOS
ENG